Positive effects of tree diversity on tropical forest restoration in a field-scale experiment - Veryard, R; Wu, J; O'Brien, MJ; Anthony, R; Both, S; Burslem, DFRP; Chen, B; Fernandez-Miranda Cagigal, E; Godfray, HCJ; Godoong, E; Liang, S; Saner, P; et al. (American Association for the Advancement of Science, 2023)
Experiments under controlled conditions have established that ecosystem functioning is generally positively related to levels of biodiversity, but it is unclear how widespread these effects are in real-world settings and whether they can be harnessed for ecosystem restoration. We used remote-sensing data from the first decade of a long-term, field-scale tropical restoration experiment initiated in 2002 to test how the diversity of planted trees affected recovery of a 500-ha area of selectively logged forest measured using multiple sources of satellite data. Replanting using species-rich mixtures of tree seedlings with higher phylogenetic and functional diversity accelerated restoration of remotely sensed estimates of aboveground biomass, canopy cover, and leaf area index. Our results are consistent with a positive relationship between biodiversity and ecosystem functioning in the lowland dipterocarp rainforests of SE Asia and demonstrate that using diverse mixtures of species can enhance their initial recovery after logging.